2009
DOI: 10.1002/mrm.22161
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating SENSE using compressed sensing

Abstract: Both parallel MRI and compressed sensing (CS) are emerging techniques to accelerate conventional MRI by reducing the number of acquired data. The combination of parallel MRI and CS for further acceleration is of great interest. In this paper, we propose a novel method to combine sensitivity encoding (SENSE), one of the standard methods for parallel MRI, and compressed sensing for rapid MR imaging (SparseMRI), a recently proposed method for applying CS in MR imaging with Cartesian trajectories. The proposed met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
390
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 416 publications
(409 citation statements)
references
References 33 publications
9
390
0
Order By: Relevance
“…; generated by alternately solving Eqs. [5] and [7] from any starting point (I 0 ,Î 0 ) converges to (I a ,Î a ), a solution of [4], and the convergence rate is linear, that is,…”
Section: Decomposition Of a Complex Problem Into Two Easier Subproblemsmentioning
confidence: 99%
See 3 more Smart Citations
“…; generated by alternately solving Eqs. [5] and [7] from any starting point (I 0 ,Î 0 ) converges to (I a ,Î a ), a solution of [4], and the convergence rate is linear, that is,…”
Section: Decomposition Of a Complex Problem Into Two Easier Subproblemsmentioning
confidence: 99%
“…For both conventional SENSE (1) and prior information regularized SENSE (26), the noise decorrelation is a routine step. When a Cartesian trajectory is used, model [4] can be further improved by introducing spatially adaptive weights to the regularization term. As the g-factor map (1) is available from the initial I-subproblem, this noise distribution information can be used to improve the effectiveness of Î-subproblem.…”
Section: Self-feeding Sparse Sensementioning
confidence: 99%
See 2 more Smart Citations
“…We also observed from some of the patients studies that at high acceleration rates, the strong fat signals from the chest and/or the back regions were more overlapped onto the heart region. The CS regularization power was increased for those studies and sometimes moderate residual artifacts 75 could still be observed. In the future, techniques such as fat-saturation RF pulses or outer-volume suppression preparation can be adopted to decrease the influence of the strong fat signals from regions that are not of interest.…”
Section: Discussionmentioning
confidence: 97%